The utilization and outcome of diagnostic, predictive, and prenatal genetic testing for huntington disease in johannesburg, South Africa - Sizer, Elaine B; Haw, Tabitha; Wessels, Tina-Marié; Kromberg, Jennifer G R; Krause, Amanda (Genetic testing and molecular biomarkers, 2012)
Huntington disease (HD) is an autosomal dominant neurodegenerative disorder for which genetic counseling and testing are available in South Africa. The purpose of this study was to assess the utilization of the services available in Johannesburg for diagnostic, predictive, and prenatal genetic testing and counseling for HD and the characteristics of the patients who use them. A retrospective study was conducted using records of patients (n=287) who had genetic counseling and/or testing for HD through the Division of Human Genetics, National Health Laboratory Service and University of the Witwatersrand, Johannesburg, between January 1998 and December 2006. Age, gender, number of children, ethnicity, and test results were analyzed. Of the 287 patients included in this study, 77% had diagnostic testing, 20% predictive, and 3% prenatal testing. In the diagnostic group, 47% of subjects tested positive for HD1 and 9% for HDL2 (all Black or of mixed ancestry). Altogether, 66.7% of subjects in the predictive group had testing and 39.5% were positive. In both groups, White subjects were overrepresented. In seven prenatal tests, three fetuses (including a set of twins) tested positive for HD and termination of pregnancy was requested. The HD services for predictive and prenatal testing appear to be underutilized, especially by Black individuals, possibly because of lack of awareness among these individuals and among healthcare providers and/or a lower HD prevalence in this group. Recognition of and testing for HDL2 is important in South Africa's large Black population, and HD testing services cannot be considered complete unless testing for both HD1 and HDL2 are undertaken.